2003
DOI: 10.1074/jbc.m211759200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis and Molecular Modeling of the Allosteric Binding Site of a Novel, Selective, Noncompetitive Antagonist of the Metabotropic Glutamate 1 Receptor

Abstract: A model of the rmGlu1 seven-transmembrane domain complexed with a negative allosteric modulator, 1-ethyl-2-methyl-6-oxo-4-(1,2,4,5-tetrahydro-benzo[d]azepin-3-yl)-1,6-dihydro-pyrimidine-5-carbonitrile (EM-TBPC) was constructed. Although the mGlu receptors belong to the family 3 G-protein-coupled receptors with a low primary sequence similarity to rhodopsin-like receptors, the high resolution crystal structure of rhodopsin was successfully applied as a template in this model and used to select residues for site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
155
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(168 citation statements)
references
References 37 publications
(55 reference statements)
12
155
0
Order By: Relevance
“…Like in Rhodopsine, a 8 th amphipatic a-helix is predicted in class-C GPCRs after transmembre domain 7 (Pin et al, 1994), and several 3D models generated based on the crystal structure of rhodopsine are consistent with mutagenesis data (Pagano et al, 2000;Malherbe et al, 2003).…”
Section: General Structure Of Class-c Gpcrssupporting
confidence: 51%
“…Like in Rhodopsine, a 8 th amphipatic a-helix is predicted in class-C GPCRs after transmembre domain 7 (Pin et al, 1994), and several 3D models generated based on the crystal structure of rhodopsine are consistent with mutagenesis data (Pagano et al, 2000;Malherbe et al, 2003).…”
Section: General Structure Of Class-c Gpcrssupporting
confidence: 51%
“…In summary, six residues (N750 45.54 , V757 5.47 , W798 6.48 , F801 6.51 , Y805 6.55 , and T815 7.39 ) are crucial in the binding of EM-TBPC to rmGlu1. 48 These experimental site-directed mutational studies provide strong evidence for overlapping binding sites of the three allosteric modulators. Despite the inevitably simplistic picture of the GPCR function used here, the described experimental findings demonstrate the practical usefulness of the LPV methodology even for class C GPCR receptors: the LPV methodology provides suggestions for mutational analysis studies and accelerates the mapping of binding sites of GPCR ligands in the TM region.…”
Section: Functional Conservation Profiles Of Tm Helices In Classmentioning
confidence: 87%
“…Homology modeling, docking analysis and mutagenesis studies have shown that nine conserved amino acid residues in the 7TM of T1R3 are involved in allosteric modulator binding. The corresponding residues have also been found in the 7TM of CaS [60][61][62][63] and mGlu receptors [64][65][66] . This implies that class C GPCRs share a common binding site for allosteric modulators.…”
Section: Tm Allosteric Sitesmentioning
confidence: 94%